Q: How do you factor 6a 6b?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

Divide by 6a: 6a(a + 3b)

Consider a=b , multiply by 94 on both sides,I.e 94a=94b. 100a-6a=100b-6b. 100a-100b=-6b+6a. 100(a-b)=6(a-b);100=6(a-b)/(a-b);their fore 100=6

6a squared-8ab+2a factor completely and check mentally

6a^2 - 6ab + 7a^2 = 13a^2 - 6ab = a * (13a - 6b)

if you mean a^5*3b^9*6a^1, the simplified form is 18a^6b^9

Related questions

6(a+b)

2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b

it roughly about 6a and 6b

An expression consisting of 2 terms. 6A + 6B.

Divide by 6a: 6a(a + 3b)

Consider a=b , multiply by 94 on both sides,I.e 94a=94b. 100a-6a=100b-6b. 100a-100b=-6b+6a. 100(a-b)=6(a-b);100=6(a-b)/(a-b);their fore 100=6

6A-6B flanges are ring type joint which is not developed for face to face make up, where the bolting forces act on gasket. 6A-6BX flanges are also ring type joint but it is developed with raised face hence the bolting forces act on this raised face and not on the gasket if it is properly placed. And also the raised prevent the flange damage from excessive bolting torque.

The GCF is 6a.

6a squared-8ab+2a factor completely and check mentally

Yes.

6a^2 - 6ab + 7a^2 = 13a^2 - 6ab = a * (13a - 6b)

For him he is doing fine.